Avaliação e controle de mais-valias decorrentes de decisões de planeamento - Emília Malcata Rebelo (2009)
This article makes an analysis of the impact that planning decisions exert on land and real estate prices, and how surplus-values introduced by these decisions may be recovered and managed on behalf of the social welfare and the promotion and strengthening of regional and urban development. It is proposed a methodology that allows the quantification of these surplus-values, considering the different factors that intervene in land and real estate price settlement, the inter-relations between these prices, the evolution of land uses, and the behaviour of different agents involved in property markets. Reflections and conclusions are drawn concerning fiscal and planning implications from this analysis, in order to warrant the availability of land for the different kinds of uses at acceptable prices, fostering the initiative of developers, promoters and builders, and preventing speculative behaviours.